Strategic Management, Economic Development and Social Identities Constructively to Promote Identity of Border Tourism of Kanchanaburi Province - Mukda, Wipada; Boonloison, Rachen; Sombun, Sarinya (Dusit Thani College Journal, 2020)
This research aims to (1) study the external and internal environment of the creative economic and social development to promote identity of border tourism of Kanchanaburi province and (2) suggest ways to promote identity of border tourism of Kanchanaburi province. The sample consisted of 385 entrepreneurs and 40 related interview. The instrument used in the research was a questionnaire. The statistics analysis used in the research were percentage, mean, standard deviation, and the content analysis and swot analysis from the interviews were analyzed and interpreted. The research found that: 1) Strength; there are many natural, cultural, and historical tourist attractions, Weakness; the internal management for tourist attractions is insufficient and the environment of tourist attractions are deteriorated, Opportunities; there are free trade and investment, Threat; there are limited budgets for the development. 2) Directions for promoting border tourism identity should be cooperation from government organization, private sector, people and media in order to create an understanding that leads to the cooperation in trading, investment, the expansion of transportation, the development of infrastructure, and the expansion of cooperation with neighboring countries in tourism.